Odpowiedzi

2010-03-25T20:21:43+01:00
2a-3b+3a+4b-4a=a+b

5xy-3x+2y+2xy+x-2y-6xy=xy-2x

2x+3y-2xy+x-2x-3y+4xy=x+2xy

2a+b-ab2 -3+4-b+a2b - 2a=1-ab2+a2b

xy-y-6+x- -6+xy-y=2xy-2y+x-12

2x+(3x-5)=2x+3x-5=5x-5

4a-(b-3a)=4a-b+3a=7a-b

(3x-2xy-1)-(-5x-2xy+8)=3x-2xy-1+5x+2xy-8=8x-1

licze na naj;);**
2010-03-25T20:22:07+01:00
2a-3b+3a+4b-4a= a+b

5xy-3x+2y+2xy+x-2y-6xy= 1xy-2x

2x+3y-2xy+x-2x-3y+4xy= x+2xy

2a+b-ab2(do kwadratu) -3+4-b+a2(do kwadratu)b - 2a= -ab² +1+a²b

xy-y-6+x- -6+xy-y=2xy-2y+x

2x+(3x-5)=5x-5

4a-(b-3a)=7a-b

(3x-2xy-1)-(-5x-2xy+8)= 8x-9


2010-03-25T20:25:00+01:00
2a-3b+3a+4b-4a =a+b
5xy-3x+2y+2xy+x-2y-6xy = xy-2x
2x+3y-2xy+x-2x-3y+4xy = x+2xy
2a+b-ab²-3+4-b+a²b-2a = -ab²+1+a²b
xy-y-6+x-(-6)+xy-y = xy-y-6+x+6+xy-y = 2xy-2y+x
2x+(3x-5) = 2x+3x-5 = 5x-5
4a-(b-3a) = 4a-b+3a = 7a-b
(3x-2xy-1)-(-5x-2xy+8) = 3x-2xy-1+5x+2xy-8 = 8x-9